Growth factors improve the proliferation of Jeju black pig muscle cells by regulating myogenic differentiation 1 and growth-related genes - Park, Jinryong; Lee, Jeongeun; Song, Ki-Duk; Kim, Sung-Jo; Kim, Dae Cheol; Lee, Sang Cheol; Son, Young June; Choi, Hyun Woo; Shim, Kwanseob (Animal bioscience, 2021)
Objective: The growth rate of pigs is related to differentiation and proliferation of muscle cells, which are regulated by growth factors and expression of growth-related genes. Thus, the objective of this study was to establish optimal culture conditions for Jeju black pig (JBP) muscle cells and determine the relationship of various factors involved in muscle growth with the proliferation of JBP muscle cells. Methods: Muscles were taken from the femur skeletal muscle of JBP embryos. After isolation of the muscle cells, cells were cultured in a 6-well plate under four different culture conditions to optimize culture conditions for JBP muscle cells. To analyze proliferation rate of JBP muscle cells, these muscle cells were seeded into 6-well plates at a density of 1.5×105 cells per well and cultured for 3 days. Western blot and quantitative real-time polymerase chain reaction were applied to verify the myogenic differentiation 1 (MyoD) expression and growth-related gene expression in JBP muscle cells, respectively. Results: We established a muscle cell line from JBP embryos and optimized its culture conditions. These muscle cells were positive for MyoD, but not for paired box 7. The proliferation rate of these muscle cells was significantly higher in a culture medium containing bFGF and epidermal growth factor + basic fibroblast growth factor (EGF+bFGF) than that without a growth factor or containing EGF alone. Treatment with EGF and bFGF significantly induced the expression of MyoD protein, an important transcription factor in muscle cells. Moreover, we checked the changes of expression of growth-related genes in JBP muscle cells by presence or absence of growth factors. Expression level of collagen type XXI alpha 1 gene was changed only when EGF and bFGF were added together to culture media for JBP muscle cells. Conclusion: Concurrent use of EGF and bFGF increased the expression of MyoD protein, thus regulating the proliferation of JBP muscle cells and the expression of growth-related genes.